Protocol for a systematic review of the impact of resuscitation fluids on the microcirculation after haemorrhagic shock in animal models. Issue 1 (December 2015) - Naumann, David; Dretzke, Janine; Hutchings, Sam; Midwinter, Mark
Abstract Background Modern resuscitation strategies following haemorrhagic shock are influenced by global haemodynamic parameters such as blood pressure and cardiac output. Microcirculatory dysfunction in this context may persist even after restoration of satisfactory global parameters. Additional monitoring of the microcirculatory function may therefore be warranted in order to facilitate goal-directed therapy at a tissue oxygenation level. Although such a phenomenon is recognised in the case of sepsis, clinical evidence regarding the behaviour of the microcirculation following the delivery of resuscitation fluids after haemorrhagic shock is sparse. A summation of the current state of pre-clinical evidence is justified in order to direct avenues for future clinical research. Methods/design Systematic review methodology will be utilised in order to identify relevant studies, assess for bias, and extract data for analysis. Medical databases will be searched to find pre-clinical studies that monitor the microcirculatory function following haemorrhagic shock and subsequent fluid resuscitation. Different fluid types (e.g. blood products, crystalloid, and colloid fluids) will be compared. The search strategy will combine terms for the animal model, resuscitation fluid, and microcirculatory parameters. Randomised and non-randomised experiments, as well as case series, will be eligible for inclusion. Specific quality assessment tools for pre-clinical research will be used depending on study design. A combination of narrative and meta-analysis techniques will be used for the synthesis of data. Discussion The choice of type, sequence, and quantity of resuscitation fluid following haemorrhagic shock is controversial, and the optimal strategy for restoration of microcirculatory function is yet unknown. A detailed examination of pre-clinical data regarding the microcirculation is timely and will enable a focussed approach to clinical research for the improvement of resuscitation following haemorrhagic shock. Systematic review registration Collaborative Approach to Meta Analysis and Review of Animal Data from Experimental Studies (CAMARADES )